Proportion of night eating syndrome in Arab population of Oman. Issue 1 (December 2015) - Zadjali, Fahad; Al-Bulushi, Aaisha; AlHassani, Fatma; Al Hinai, Mustafa
Abstract Objective Globally obesity has reached epidemic proportions with alarming rates in the Arabian Gulf countries. The impact of behavioral eating habits and in particular night eating syndrome (NES) have not been emphasized in the region. This study assessed the proportion of NES in an Omani Arab adult population sample. Method A night eating syndrome questionnaire (NEQ) was distributed to Omani adults above the age of 20. Results Out of the 454 respondents, 26.4 % endorsed evening hyperphagia while nocturnal ingestion was present in 4.7 % of the respondents. In addition, 1.5 % of the respondents met the NES criteria. Conclusions and implications The proportion of NES in Omani adult population is similar to the reported rates in general world populations. In conclusion, night eating syndrome is present in the Omani Arab adults and should be taken into account in national management for increased obesity trends in the region.